Textile depilling : superior finishing using cellulose-binding domains with residual enzymatic activity - Ramos, Reinaldo Rodrigues (2007)
Textile fabric depilling is an important industrial application of cellulases. The depilling effect and achievement of desirable touch properties are among the applications sought by users. This process, although effective, is associated with significant tensile strength loss. The depilling mechanism is still a subject of controversy. In this work, we introduce a new perspective in understanding of the depilling mechanism, specifically we consider the contribution of interfacial properties. Cellulose Binding Domains (CBDs) obtained by ultrafiltration after digestion with a protease, were used in depilling experiments. Compared with cellulose, the performance of CBDs was very positive. In fact, when using CBD with residual hydrolytic activity, it was possible to achieve superior depilling treatments.